2012
DOI: 10.1007/s12550-012-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

Lack of micronuclei induction by fumonisin B1 mycotoxin in BALB/c mice

Abstract: The genotoxic potential of fumonisin B(1) (FB(1)) in vivo in BALB/c mice (male and female) was assessed by induction of micronuclei (MN) formation in bone marrow polychromatic erythrocytes. The ratio of polychromatic erythrocytes to normochromatic erythrocytes (PCE/NCE) was also determined. Mice were injected intraperitoneally (i.p.) with FB(1) at a low dose (0.1 mg kg(-1) body mass), middle dose (1.0 mg kg(-1) body mass) and high dose (10 mg kg(-1) body mass) as single and multiple doses in normal saline to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[12,13] Several studies in rodents have shown that FB 1 promotes pre-neoplastic lesions in the liver, suggesting a role for FB 1 -induced genotoxicity. [14] Recently, Chuturgoon et al [15] reported that FB 1 induces global DNA hypomethylation and histone demethylation in human hepatoma cells that causes chromatin instability and may lead to liver tumourigenesis. FB 1 is resistant to conditions normally used in food processing and, therefore, poses a significant hazard to human and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Several studies in rodents have shown that FB 1 promotes pre-neoplastic lesions in the liver, suggesting a role for FB 1 -induced genotoxicity. [14] Recently, Chuturgoon et al [15] reported that FB 1 induces global DNA hypomethylation and histone demethylation in human hepatoma cells that causes chromatin instability and may lead to liver tumourigenesis. FB 1 is resistant to conditions normally used in food processing and, therefore, poses a significant hazard to human and animal health.…”
Section: Introductionmentioning
confidence: 99%
“…FB 1 did not cause an increase in the frequencies of micronucleated erythrocytes in the BALB/c mice neither in single nor in multiple dose studies (Karuna and Rao, 2013). single dose or repeated injections of pure FB 1 (0.1, 1.0 and 10 mg/kg bw).…”
Section: Genotoxicity Studiesmentioning
confidence: 73%
“…Controls and positive controls were injected with single doses of saline and mitomycin C, respectively. FB 1 did not cause an increase in the frequencies of micronucleated erythrocytes in the BALB/c mice neither in single nor in multiple dose studies (Karuna and Rao, 2013). Pellanda et al (2012) fed groups of Wistar rat dams diets containing 0.9 mg/kg folate, 0.04 mg/kg vitamin B 12 and 2,100 mg/kg choline either without (control, n = 13) or with addition of pure FB 1 at 4 lg/kg bw per day (n = 2) and to methyl-deficient diets (MDD, 0.01 mg/kg folate, 0 mg/kg vitamin B and 0.06 mg/kg choline) either without (n = 15) or with addition of 4 lg FB 1 /kg bw per day (n = 3), for 1 month before mating.…”
Section: Genotoxicity Studiesmentioning
confidence: 74%
See 1 more Smart Citation
“…While FB 1 is not a genotoxic carcinogen, it does increase micronucleus frequency and single-strand DNA breaks as assessed by the comet assay in a range of human cell lines. 19,20 The immediate response to single-strand DNA breaks involves PARP-1 induction of DNA repair, termed base excision repair (BER), and occurs in four steps that include the recruitment of DNA glycosylase, apurinic/apyrimidinic (AP) endonuclease, DNA polymerase and DNA ligase. Oxoguanine glycosylase 1 (OGG1) is a DNA glycosylase that recognizes and removes the 8-oxyguanine (8-OH-G) that is formed following exposure to FB 1.…”
Section: Introductionmentioning
confidence: 99%